Prognostic value of automated bone scan index for predicting overall survival among bone metastatic castration resistant prostate cancer patients treated with radium‐223. Issue 1 (5th September 2020) - Miyoshi, Yasuhide; Tsutsumi, Sohgo; Kawahara, Takashi; Yasui, Masato; Uemura, Koichi; Yoneyama, Shuko; Yokomizo, Yumiko; Hayashi, Narihiko; Yao, Masahiro; Uemura, Hiroji
Abstract: Introduction: The objective of this study was to evaluate automated bone scan index (aBSI) as a prognostic biomarker for overall survival (OS) in bone‐metastatic, castration‐resistant prostate cancer (mCRPC) patients treated with radium‐223 (Ra‐223). Materials and methods: We identified 42 men treated with Ra‐223 for mCRPC. We investigated aBSI as an independent prognostic factor by multivariate analysis. Moreover, we evaluated the prognostic value of the aBSI after 12 weeks after the first cycle of Ra‐223 administration and aBSI change from baseline to after 12 weeks (ΔBSI). Results: Median baseline PSA and aBSI were 42.8 ng/mL and 1.5%, respectively. Median OS was 20.7 months. Multivariate analysis showed that baseline aBSI was a significant prognostic factor for OS. The aBSI at 12 weeks after first Ra‐223 administration also exhibited significant prognostic value for OS, while we found no evidence of prognostic value for ΔBSI. Conclusions: Baseline aBSI may be a significant prognostic factor for OS in bone‐metastatic CRPC patients treated with Ra‐223.